2023
DOI: 10.3390/microorganisms11071733
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Osmolytes and Membrane Lipids in the Adaptation of Acidophilic Fungi

Abstract: Acidophiles maintain near-neutral intracellular pH using proton pumps. We have suggested the protective role of osmolytes and membrane lipids in the adaptation to an acidic environment. Previously we have observed, for the first time, high levels of trehalose in acidophilic basidiomycete Sistotrema brinkmannii. Here, we have studied the composition of both osmolytes and membrane lipids of two more acidophilic fungi. Trehalose and polyols were among the main osmolytes during growth under optimal conditions (pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Thus, a high degree of unsaturation of the phospholipid fraction can be observed (about 1.5), which is usually characteristic of psychrophilic fungi [ 42 , 43 ]. It has also been previously shown that in P. gigantea , the degree of unsaturation remained constant both in growth dynamics and under unfavorable pH conditions [ 25 ]. The data obtained suggest that the mechanism for changing the degree of unsaturation is not involved in the adaptation of P. gigantea to either the pH factor or HS, CS, or OS.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Thus, a high degree of unsaturation of the phospholipid fraction can be observed (about 1.5), which is usually characteristic of psychrophilic fungi [ 42 , 43 ]. It has also been previously shown that in P. gigantea , the degree of unsaturation remained constant both in growth dynamics and under unfavorable pH conditions [ 25 ]. The data obtained suggest that the mechanism for changing the degree of unsaturation is not involved in the adaptation of P. gigantea to either the pH factor or HS, CS, or OS.…”
Section: Discussionmentioning
confidence: 97%
“…In our studies, we have shown that PAs, which are minor components in non-extremophiles [ 44 ], are present in extremophiles, either as predominant or as one of the main membrane lipids [ 24 , 25 , 45 , 46 , 47 ]. PAs are multifunctional and poorly studied compounds, being a key metabolite of lipogenesis and performing regulatory and structural functions [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations